P192 Syndemics among gay, bisexual and other men who have sex with men in the united kingdom and the republic of ireland: empirical evidence of clustered health inequalities. (8th June 2017) - McDaid, Lisa; McAloney-Kocaman, Kareena; Flowers, Paul; Boydell, Nicola; Coia, Nicky; Kerr, Yvonne; Frankis, Jamie
Abstract : Introduction: Gay men experience a multiple burden of ill health in relation to sexual health, mental health and substance use and there is growing recognition that these could cluster as syndemic health inequalities. Few studies (outside the USA) have addressed the co-occurrence of such negative health outcomes. We examine empirical evidence of syndemic health outcomes in an online cross-sectional survey of MSM. Methods: Self-report data on sexual, mental and physical health outcomes from the SMMASH2 survey of 3373 MSM in Scotland, England, Wales, Northern Ireland and the Republic of Ireland in 2016 were used to derive a measure of syndemic ill health. Results: Overall, 68.2% reported at least one sexual health outcome, 60.4% reported at least one mental health outcome, and 61.0% reported at least one physical health outcome. There was significant co-occurrence of outcomes, with 67.0% reporting multiple health outcomes; 42.0% reporting two, and 27.0% reporting all three. There was statistically significant clustering of the behaviours at all levels. When examining all three outcomes concurrently, all were clustered with greater prevalence than expected if the outcomes where independent (O/E Ratio=1.07; 95% Confidence Interval 1.004 –1.14). Discussion: Clustering of poor sexual, mental and physical health provides evidence of syndemic health inequalities in communities of gay, bisexual and other MSM surveyed online (at levels significantly higher than the nationally estimated prevalence of 8.4%). Current health improvement efforts are often characterised by disjointed services, which should be reconfigured to ensure a holistic approach to addressing the complex, multi-faceted, interrelated issues affecting these communities.